2010
DOI: 10.1117/12.846270
|View full text |Cite
|
Sign up to set email alerts
|

Top coat less resist process development for contact layer of 40nm node logic devices

Abstract: ArF immersion lithography has been introduced in mass production of 55nm node devices and beyond as the post ArF dry lithography. Due to the existence of water between the resist film and lens, we have many concerns such as leaching of PAG and quencher from resist film into immersion water, resist film swelling by water, keeping water in the immersion hood to avoid water droplets coming in contact with the wafer, and so on. We have applied to the ArF dry resist process an immersion topcoat (TC) process in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The transient formation of swelling layer is considered to play an important role for the defect formation. [28][29][30] This study revealed that the tendency of dissolution depends on both the molecular weight and molecular weight dispersion of the polymer. Dissolution occurs through the swelling of the polymer bulk and the diffusion of polymer chains into the solution bulk.…”
Section: Resultsmentioning
confidence: 86%
“…The transient formation of swelling layer is considered to play an important role for the defect formation. [28][29][30] This study revealed that the tendency of dissolution depends on both the molecular weight and molecular weight dispersion of the polymer. Dissolution occurs through the swelling of the polymer bulk and the diffusion of polymer chains into the solution bulk.…”
Section: Resultsmentioning
confidence: 86%
“…Resist swelling was suggested as one of the causes of defect generation. [17][18][19] In the development of EUV resists, the dissolution kinetics was investigated by high-speed atomic force microscopy. It was revealed by in situ observation that the thickness of the exposed area was doubled at most during development.…”
Section: Introductionmentioning
confidence: 99%
“…5,6) The clarification of the development processes is a key to the improvement of resist performance. [6][7][8][9] In particular, understanding of the dissolution kinetics of acidic polymers such as PHS is important, because they are the essential core for the dissolution during development.…”
Section: Introductionmentioning
confidence: 99%